Burnout among postgraduate medical trainees in Lebanon: Potential strategies to promote wellbeing - Yacoubian, Aline; Degheili, Jad A.; Der-Boghossian, Asdghig; Najdi, Jad; Andraos, Rebecca; Zeineldine, Salah (Frontiers in Public Health, 2023)
Objective Burnout is a widespread issue in healthcare for many years. Lebanon combatted political and economic crises before the coronavirus disease 2019 (COVID-19) pandemic, in addition to the port explosion in August 2020. The study aimed to identify the determinants of personal burnout, patient-burnout, and work-related burnout among Postgraduate medical trainees (PGMT) and evaluate its relationship with sociodemographic characteristics. Design A cross-sectional study utilized the Copenhagen Burnout Inventory (CBI) involving electronic, voluntary, and anonymous survey. The survey was completed by 188 PGMT including residents and fellows from all specialties and all levels of training. Results The prevalence rates are 68.6% for personal burnout, 63.3% for work-related burnout and 35.1% for patient-related burnout. Conclusion Results improve our understanding of the phenomenon of burnout, and the role of program leadership in shaping the impact of burnout on training and promoting well-being of PGMT. Discussion focuses on providing potential well-being strategies for program directors to follow for mitigating burnout.